Electrochemical fabrication and evaluation of a self-standing carbon nanotube/carbon fiber composite electrode for lithium-ion batteries. Issue 57 (16th October 2019) - Liu, Yi-Hung; Lin, Heng-Han; Tsai, Tsung-Yu; Hsu, Chun-Han
Abstract : A binder-free CNT/CF composite electrode is developed via electrophoretic deposition, offering favorable electrochemical performances and stability as a self-standing lithium-ion battery anode. Abstract : A binder-free self-standing carbon nanotube (CNT)/carbon fiber (CF) composite electrode, which has been developed using an electrophoretic deposition approach, was utilized as a lithium-ion battery anode. The morphology of the CNT/CF composite has been examined using scanning electron microscopy, and the results indicated that a CNT layer uniformly deposited on the CFs. The thickness and density of the CNT layer increased as the electrodeposition time increased, while overdeposition caused the CNT layer to exfoliate. Electrochemical evaluation revealed that the specific capacity, cycling stability, and rate capability of the CNT/CF anode were superior to those of the CF anode. The electrochemical impedance analysis results further revealed that the solid/electrolyte interface resistance and interface resistance induced by the oxygen-containing surface functional groups of CFs dominated the impedance of the anode. However, these resistance values could be potentially reduced via CNT surface modification, which could lead to the enhanced electrochemical performance of the CNT/CF anode. Our findings should open new avenues for the potential use of the CNT/CF composite as a self-standing anode for lithium-ion battery applications.